Raman scattering, differential scanning calorimetry and Nd3+ spectroscopy in alkali niobium tellurite glasses - Cassanjes, F. C.; Messaddeq, Younes [UNESP]; de Oliveira, LFC; Courrol, L. C.; Gomes, L.; Ribeiro, SJL (Elsevier B.V., 1999)
Alkali niobium tellurite glasses have been prepared and some of their properties measured by differential scanning calorimetry and Raman scattering. The vitreous domain was established in the pseudo ternary phases diagram for the system TeO2-Nb2O5-(0.5K(2)O-0.5Li(2)O). Raman scattering shows that for samples in the TeO2 rich part of the phase diagram the vitreous structure is composed essentially of (TeO4) units connected by the vertices, as in the alpha-TeO2 crystal. The addition of alkali and niobium oxides causes depolymerization to occur with structures composed essentially of (TeO3) and (NbO6) units. Samples with the composition (mol%) 80TeO(2)-10Nb(2)O(5)-5K(2)O-5Li(2)O, stable against crystallization, were prepared containing up to 10% mol Nd3+. The addition of this oxide increases the rigidity of the vitreous network shifting characteristic temperatures to higher temperatures. For the 10% Nd3+ sample amorphous phase separation is assumed to exist from the observation of two glass transition temperatures. Spectroscopic properties such as Judd-Ofelt Omega(lambda) intensity parameters, radiative emission probabilities, and induced emission cross sections were calculated. From these results and also from the emission quenching observed as a function of Nd3+ concentration, we suggest that these glasses could be utilized in optical amplifying devices. (C) 1999 Elsevier B.V. B.V. All rights reserved.